Distributed Safety Controllers for Web Services - Sandholm, Anders B.; Schwartzbach, Michael I. (BRICS Report Series, 1997)
We show how to use high-level synchronization constraints, written in a version of monadic second-order logic on finite strings, to synthesize safety controllers for interactive web services. We improve on the naïve runtime model to avoid state-space explosions and to increase the flow capacities of services.